2008
DOI: 10.1158/1535-7163.mct-07-2116
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 and Chk2 are differentially involved in homologous recombination repair and cell cycle arrest in response to DNA double-strand breaks induced by camptothecins

Abstract: Camptothecins (CPT) activate S or G 2 -M arrest and the homologous recombination (HR) repair pathway in tumor cells. In this process, both checkpoint kinases 1 and 2 (Chk1 and Chk2, respectively) are activated, but their differential roles, especially in the coordination of checkpoint and repair control, and potential clinic relevance remain to be fully elucidated. In this study, the repairable double-strand breaks were induced in human colon cancer HCT116 cells by 1-h exposure to 25 or 100 nmol/L CPT and its … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…HCT-116 cells were cultured in the presence of FdUrd or FTD at IC 50 concentrations for 24 and 72 hours, and ssDNA and dsDNA breaks were evaluated by alkaline-and neutral-comet assays. As reported previously (28,29), a significant increase in the mean score of the tail moment was observed in alkaline-and neutral-comet assays after camptothecin treatment ( Supplementary Fig. S7).…”
Section: Ftd-induced Decrease Of Cyclin B1 Protein Is Dependent On P21supporting
confidence: 85%
“…HCT-116 cells were cultured in the presence of FdUrd or FTD at IC 50 concentrations for 24 and 72 hours, and ssDNA and dsDNA breaks were evaluated by alkaline-and neutral-comet assays. As reported previously (28,29), a significant increase in the mean score of the tail moment was observed in alkaline-and neutral-comet assays after camptothecin treatment ( Supplementary Fig. S7).…”
Section: Ftd-induced Decrease Of Cyclin B1 Protein Is Dependent On P21supporting
confidence: 85%
“…Curcumin treatment modulates expression of G2/M cell cycle regulatory proteins DNA damage generally leads to the activation of the ATM/ATR pathway (Molinari, 2000;Abraham, 2001;Lukas et al, 2001;Huang et al, 2008). To further delineate the molecular mechanism of curcumin-mediated G2/M arrest, we determine its effect on the key-signaling proteins of this pathway.…”
Section: Curcumin Causes Dna Damage and Induces Apoptosismentioning
confidence: 98%
“…This study also demonstrated that Eupatilin arrests the cell cycle as a result of the DNA damage and indicated that Eupatilin induced growth inhibition is likely to involve the modulation of cell cycle progression in A375 cells. During DNA damage, cells are blocked in G2/M phase to provide time to repair damaged DNA (Molinari 2000;Abraham, 2001), or lead to apoptotic cell death in case of severe DNA damage (Huang et al, 2008).…”
Section: Eupatilin Induces Cell Cycle Arrest Of A375 Melanoma Cellsmentioning
confidence: 99%